Mendelian randomization shows causal effects of birth weight and childhood body mass index on the risk of frailty - Cui, Junhao; Fu, Shuqin; Zhu, Lin; Li, Peng; Song, Chunlan (Frontiers in Public Health, 2024)
Background The association between birth weight and childhood body mass index (BMI) and frailty has been extensively studied, but it is currently unclear whether this relationship is causal. Methods We utilized a two-sample Mendelian randomization (MR) methodology to investigate the causal effects of birth weight and childhood BMI on the risk of frailty. Instrumental variables (p < 5E-08) strongly associated with own birth weight (N = 298,142 infants), offspring birth weight (N = 210,267 mothers), and childhood BMI (N = 39,620) were identified from large-scale genomic data from genome-wide association studies (GWAS). The frailty status was assessed using the frailty index, which was derived from comprehensive geriatric assessments of older adults within the UK Biobank and the TwinGene database (N = 175,226). Results Genetically predicted one standard deviation (SD) increase in own birth weight, but not offspring birth weight (maternal-specific), was linked to a decreased frailty index (β per SD increase = −0.068, 95%CI = −0.106 to −0.030, p = 3.92E-04). Conversely, genetically predicted one SD increase in childhood BMI was associated with an elevated frailty index (β per SD increase = 0.080, 95%CI = 0.046 to 0.114, p = 3.43E-06) with good statistical power (99.8%). The findings remained consistent across sensitivity analyses and showed no horizontal pleiotropy (p > 0.05). Conclusion This MR study provides evidence supporting a causal relationship between lower birth weight, higher childhood BMI, and an increased risk of frailty.